Pengaruh Kualitas dan Nilai Fungsional-Emosional-Sosial Turis terhadap Kepuasan dan Minat Kunjung Ulang (Re-Visit) pada Atraksi Wisata Taman Hiburan Pesona Trukan Tambahrejo, Purworejo - Budi Supriyanto; Sri Fajar Ayuningsih; B. Syarifudin Latif; Anak Agung Gde Agung; Jakaria Jakaria (Destinesia : Jurnal Hospitaliti dan Pariwisata, 2022)
This paper tries to find the influence of tourist perceptions and values consisting of functional, emotional and social on tourist satisfaction and interest in revisiting the tourist attraction in central java. The object in this research paper is a tourist attraction named Pesona Trukan in Bagelen District, Purworejo Regency, Central Java. The sample of this study is 100 people who were domestic tourists who visited the location of the tourist attraction. Accidental sampling method is a technique used in data collection. The data is sourced from questionnaires and is the main data used in the research. The research variables consist of (1) Tourist perceptions of tourist attractions; (2) Value perception (functional, emotional, and social); (3) Tourist satisfaction, and; (4) Interest in visiting tourists again. The analysis used in testing the relationship is the Structural Equation Model using the SmartPLS and SPSS applications. The conclusions from the analysis are: (1) Quality has a significant and positive effect on tourist functionality; (2) Quality has a significant and positive effect on tourists' emotions; (3) Quality has a significant and positive effect on social tourism; (4) Functional significant effect on tourist satisfaction; (5) Emotional has a significant effect on tourist satisfaction; (6) Social has a significant effect on tourist satisfaction; (7) Tourist satisfaction mediates the functional effect on repeat interest; (8) Tourist satisfaction mediates the emotional effect on return interest; (9) Tourist satisfaction mediates social influence on return visit interest.